STRATEGI INOVASI PADA MODEL BISNIS DALAM MENGHADAPI PERSAINGAN GLOBAL - Bima Andika, Bima Andika; Salsabilla; Agisty Fiannisa; Tiara Fitriani; Nurbaiti (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
In an effort to face increasingly fierce global competition, this article discusses the implementation of innovation strategies in company business models. Companies must continue to innovate to maintain their competitive position at the global level in a market that is constantly changing and influenced by technological advances. Various elements include innovation in business models, such as product and service development, digital transformation, and improving operational processes and customer experience. Artificial intelligence (AI), automation, and the use of big data are some of the advanced technologies that make businesses more efficient and responsive to market changes. In contrast, business models such as business to consumer, business to business, or even business to consumer are flexible and adaptable allowing companies to meet the demands of diverse markets around the world. Additionally, as consumer awareness of social and environmental issues increases, the desire for innovation becomes more important. Overall, this article shows that implementing appropriate innovations in business models can create sustainable growth opportunities and increase a company's competitiveness in the global market. This research uses a qualitative approach through literature review by looking at relevant library materials. The aim of this research is to explore the important role of innovation in products, processes and interactions with consumers, as well as understand how companies can utilize technology and overcome challenges in the face of increasingly fierce international competition. Keywords : Innovation Strategy, Business Models, Global Competition, Competitiveness, Digital Technology